Phytochemistry and Antidiabetic Activity from the Leaf Midrib of Nypa fruticans Wurm. - Rosnani Nasution; Yoon Jeon; Hadis Fadillah; Muhammad Bahi; Marianne Marianne (Universitas Gadjah Mada, 2024)
This study aims to determine the antidiabetic activity of n-hexane and ethanol extracts of Nypa fruticans leaf sheaths. The ethanol extract, with the most active antidiabetic properties from the n-hexane extract, was characterized using GC-MS. The total phenol, total flavonoid, and antioxidant properties were determined, and then the ethanol extract was fractionated. An antidiabetic activity test was carried out using the glucose tolerance method in male Swiss Webster mice. The results showed that subfraction A (the effect of fractionation of ethanol extract) was the most capable of reducing blood sugar levels, namely 247.67 mg/dL in 30 min (the activity is 98.67% compared to glibenclamide). The ethanol extract can reduce blood glucose levels by 203.34 mg/dL at 30 min (81.01% compared to glibenclamide). The results of total phenolic and total flavonoid content tests for the ethanol extract were obtained at 18.0349 mg gallic acid equivalents/g and 2.8309 mg quercetin equivalents/g, respectively. On the other hand, the IC50 antioxidant activity of the extract is 417.4399 ppm. Characterization using GC-MS on the extract showed that the dominant phytoconstituent in the extract is 4-methoxy-6-(2-propenyl)-1,3-benzodioxole, with a composition of 63.45%.